Retinoic acid receptor activity is required for the maintenance of type 1 innate lymphoid cells. (8th December 2022) - Asahi, Takuma; Abe, Shinya; Tajika, Yuya; Rodewald, Hans-Reimer; Sexl, Veronika; Takeshima, Hiroshi; Ikuta, Koichi
Abstract: Group 1 innate lymphoid cells (G1-ILCs) are innate immune effectors critical for the response to intracellular pathogens and tumors. G1-ILCs comprise circulating natural killer (NK) cells and tissue-resident type 1 ILCs (ILC1s). ILC1s mainly reside in barrier tissues and provide the initial sources of interferon-γ (IFN-γ) to prime the protecting responses against infections, which are followed by the response of recruited NK cells. Despite such distribution differences, whether local environmental factors influence the behavior of NK cells and ILC1s is unclear. Here, we show that the signaling of retinoic acid (RA), active metabolites of vitamin A, is essential for the maintenance of ILC1s in the periphery. Mice expressing RARα403, a truncated form of retinoic acid receptor α (RARα) that exerts dominant negative activity, in a lymphoid cell- or G1-ILC-specific manner showed remarkable reductions of peripheral ILC1s while NK cells were unaffected. Lymphoid cell-specific inhibition of RAR activity resulted in the reduction of PD-1 + ILC progenitors (ILCPs), but not of common lymphoid progenitors (CLPs), suggesting the impaired commitment and differentiation of ILC1s. Transcriptome analysis revealed that RARα403-expressing ILC1s exhibited impaired proliferative states and declined expression of effector molecules. Thus, our findings demonstrate that cell-intrinsic RA signaling is required for the homeostasis and the functionality of ILC1s, which may present RA as critical environmental cue targeting local type 1 immunity against infection and cancer. Abstract : Retinoic acid controls ILC1 development and functions Graphical Abstract: